Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.26442/00403660.2020.10.000736
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of autoimmune endocrine diseases in vitiligo patients

Abstract: Vitiligo is a common polygenic autoimmune disease in which the foci of depigmentation are formed on the skin and/or mucous membranes as a result of the death of melanocytes. There are several hypotheses for the pathogenesis of the disease, the leading role among them is played the autoimmune hypothesis. This review summarizes the available literature data on the prevalence and structure of comorbid endocrine autoimmune pathology in vitiligo patients. In most studies conducted in Europe, America and Asia the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…17 This theory explains the association of vitiligo with other autoimmune disorders; the most common are thyroid disorders (Graves, Hashimoto), type 1 diabetes mellitus, pernicious anemia, rheumatoid arthritis, psoriasis, alopecia areata, celiac disease, and autoimmune polyendocrine syndromes. 18-20 Other studies found a higher association with thyroid disorders than us; Pagovich et al 21 found that up to 25% of the individuals presented thyroid disease in a study carried out in New York City. Martins et al 9 in Brazil found a prevalence of 4.5%, similar to our findings (5.1%).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…17 This theory explains the association of vitiligo with other autoimmune disorders; the most common are thyroid disorders (Graves, Hashimoto), type 1 diabetes mellitus, pernicious anemia, rheumatoid arthritis, psoriasis, alopecia areata, celiac disease, and autoimmune polyendocrine syndromes. 18-20 Other studies found a higher association with thyroid disorders than us; Pagovich et al 21 found that up to 25% of the individuals presented thyroid disease in a study carried out in New York City. Martins et al 9 in Brazil found a prevalence of 4.5%, similar to our findings (5.1%).…”
Section: Discussionmentioning
confidence: 76%
“…19 Furthermore, children with vitiligo have a genetic predisposition; there are many genes related with the disease. 19,20 In our population, 12.59% of the individuals have positive family history of vitiligo. We noticed that in our study, the percentage was slightly higher in the lower age groups (0-5 and 5-9 years of age).…”
Section: Discussionmentioning
confidence: 89%
“…The presence of circulating antibodies was correlated with both a long duration of vitiligo and the onset of vitiligo at an older age, but antibody titers were not correlated with the progression, regression, or stability of vitiligo. A retrospective observational study of 700 vitiligo patients highlighted the lack of a clear difference in response to therapy or vitiligo activity in patients with other concomitant autoimmune or autoinflammatory pathologies [23] and found that forms of NSV are more commonly associated with a personal or family history of autoimmunity compared to forms of SV (segmental vitiligo) [23,38].…”
Section: Characteristics Of Age Groupsmentioning
confidence: 99%